The perspectives of high-performance athletes on mental health assessment: a mixed-methods exploratory study - Silvester, C.; Hume, P. A.; Clark, T.; Donkin, L. (International Journal of Sport and Exercise Psychology, 2025)
Epidemiological evidence has reinforced the importance of psychological screening and mental health assessment (MHA) of high-performance athletes for early identification and prevention of mental ill-health. However, there is variation in worldwide implementation of MHA. It is unclear what assessment is available to athletes and how this assessment is perceived by those within the high-performance environment in Aotearoa/New Zealand. This study sought to identify experiences Aotearoa/New Zealand high-performance athletes had with MHA, the effects of MHA, and how MHA might be improved. Seventy-four athletes answered an online, mixed-methods survey investigating this topic. Over half of all participants reported having experienced no MHA monitoring, 55% reported current screening approaches were insufficient, and 89% indicated assessments could be improved. Of those whose mental health was actively screened, 22% believed current approaches were sufficient, 47% believed that current approaches were partially sufficient, and 31% believed current MHA approaches were insufficient. Participants reported that MHA facilitates access to support, addresses mental health stigma, and has a bidirectional association with sporting and personal culture. Participants differentiated between formal and informal assessments, discussing the positive and negative features of both.